Closure of a Nonhealing Gastrocutaneous Fistula Using Argon Plasma Coagulation and Endoscopic Hemoclips - H Hameed; S Kalim; YI Khan (Canadian Journal of Gastroenterology)
A case in which a gastrocutaneous fistula developed after percutaneous endoscopic gastrostomy tube placement is presented. The fistula was first managed conservatively, then was closed by argon plasma coagulation and hemoclip placement. The patient was observed and was discharged once the gastrocutaneous fistula closed.